Implementasi Gerkan Literasi Di MI Al-Hasanah Lumban Dolok Dalam Meningkatkan Minat Baca Siswa - Ikrimah Sahuro; Khodijah Nasution; Putri Sakinah; Samriyahtul Hasanah; Wakiah Tussukria; Zumiah Safitri (ASPIRASI : Publikasi Hasil Pengabdian dan Kegiatan Masyarakat, 2024)
This research aims to determine various school literacy movement programs in fostering students' interest in reading. This type of research is qualitative (descriptive) research. Data collection techniques use listening and understanding techniques. The data validation technique uses data source triangulation. Data analysis uses data reduction, data display and drawing conclusions. The results of this research show the implementation of the school literacy movement in fostering students' interest in reading with models of implementing the school literacy movement such as adding interesting books, reading activities 15 minutes before learning, utilizing the school environment for literacy movements or reading that is rich in expanding students' knowledge and conducting questions and answers. and convey the material that is understood